The Influence of Learning Styles on Mathematical Literacy in Fifth-Grade Students: A Qualitative Study of Unit Measurement - Ayuningtyas, Sekar; Nurafni, Nurafni (Department of Mathematics Education Program IPI Garut, 2025)
Rendahnya literasi matematika siswa Indonesia menegaskan perlunya strategi pembelajaran yang sesuai dengan karakteristik belajar siswa. Penelitian ini bertujuan menganalisis hubungan gaya belajar dan kemampuan literasi matematika siswa kelas V pada materi pengukuran satuan. Pendekatan deskriptif kualitatif digunakan dengan melibatkan 30 siswa melalui kuesioner gaya belajar, tes literasi matematika, wawancara, dan observasi kelas. Data dianalisis dengan model Miles dan Huberman untuk memastikan validitas dan kedalaman interpretasi. Hasil menunjukkan gaya belajar visual mendominasi (53,3%) dengan nilai rata-rata tertinggi (79,31) dan keunggulan dalam merepresentasikan data. Gaya belajar auditori (13,3%) lebih menonjol dalam penalaran dan komunikasi verbal, sedangkan gaya belajar kinestetik (33,3%) unggul dalam penggunaan alat matematika dan penerapan praktis. Penelitian ini menegaskan pentingnya pembelajaran berdiferensiasi yang menyesuaikan modalitas belajar untuk meningkatkan pemahaman dan kinerja matematika, sekaligus memberikan rekomendasi praktis bagi guru dalam merancang pembelajaran adaptif yang mendukung program Merdeka Belajar. The low level of mathematical literacy among Indonesian students, highlights the need for teaching strategies tailored to students’ learning characteristics. This study aims to analyze the relationship between learning styles and the mathematical literacy skills of fifth-grade students on unit measurement material. A descriptive qualitative approach was employed, involving 30 students through learning style questionnaires, mathematical literacy tests, interviews, and classroom observations. Data were analyzed using the Miles and Huberman model to ensure validity and depth of interpretation. The results show that visual learning styles dominate (53.3%) with the highest average score (79.31) and strengths in data representation. Auditory learning styles (13.3%) are more prominent in reasoning and verbal communication, while kinesthetic learning styles (33.3%) excel in using mathematical tools and practical applications. This study concludes that differentiated instruction that accommodates various learning modalities is crucial for improving mathematical understanding and performance, while providing practical recommendations for teachers to design adaptive learning that supports the Merdeka Belajar program.